Let's solve the equation step-by-step and fill in the missing terms and descriptions where necessary.
-
Start with the original equation: \[ -2(-d+13)+10 = -12 \]
-
Apply the distributive property: \[ 2d - 26 + 10 = -12 \]
-
Combine like terms: \[ 2d - 16 = -12 \]
-
Add 16 to both sides (to isolate the term with \(d\)): \[ 2d = -12 + 16 \] This simplifies to: \[ 2d = 4 \]
-
Divide both sides by 2 (to solve for \(d\)): \[ d = \frac{4}{2} \] Simplifying gives: \[ d = 2 \]
Summary of the process with descriptions:
- Start with the given equation.
- Apply the distributive property.
- Combine like terms.
- Add 16 to both sides.
- Divide both sides by 2.
Final Solution: \[ d = 2 \]
Missing Descriptions Filled In:
- Apply the distributive property
- Combine like terms
- Add 16 to both sides
- Divide both sides by 2
Missing Terms Filled In:
- \(2d - 16 = -12\)
- \(2d = 4\)
- \(d = 2\)